MEMAHAMI HADITS TENTANG LA’NAT MALAIKAT TERHADAP ISTRI YANG MENOLAK AJAKAN SUAMI - Sobari sutarip (JURNAL INDO-ISLAMIKA, 2018)
The discussion about married life is an interesting discussion and becomes the focus of public attention. Islam commands to live in pairs and build a household. Islam pays serious attention to married life. Because human nature requires love and affection. Allah is in the form of male and female to live in pairs so that peace, love and compassion can be created. It is the duty of every saumi and wife to get along with their partner ma'ruf (well). However, A and building a household ark does not always run smoothly without the gravel and obstacles. This paper will discuss the life of a couple who experience disharmony in the household. Or specifically, this paper will examine the hadith about the cursing of angels against a wife who refuses her husband's invitation to have sex. In this hadith about la'nat, the steps taken by the researcher are as follows: First, compiling the hadiths that discuss related themes, especially from the poles. Second, mentakhrij and criticize the related hadiths. Third, the impression of the hadith syarh (muhaddithin) to understand the contents of the hadith. Fourth, the views of contemporary fuqoha 'and scholars on related themes. While the approach used is the fiqh approach as well as the social psychology approach and the medical approach